Penyetaraan tes soal potensi akademik berdasarkan teori respon butir menggunakan Software R di STMIK AKBA - Akbar Iskandar; Ahmad Rudi (Journal of Educational Science and Technology (EST), 2017)
This study aims to determine the quality of the package about the Academic Potential Test, to know the procedure of equalizing the package of test of Academic Potential Test and to know how to get two sets of tests that have equality with the method of testEquatigdata .. The type of research is explorative, which will reveal the equivalence of test scores based on response- Items. Tithe equivalence procedure, horizontal equalizer selection, common item nonequivalent group equalization selection, third parameter estimation using 2P model (different power and difficulty level) and four equalization process using testEquatingData. Results Equivalence tests with the EQuestData method based on the grain response theory using the 2 parameter model, indicating that the average difficulty level on both packages differs from the packet value of 01 (-1.32934) and the packet value 02 (-2.63645). While the difference between the two packages is different and shows that it can not distinguish the ability of the participants, between high ability and low participant ability, based on the value of package 01 (-0.26831) and package 02 (-0.37774).